Behavior of Piled Raft Foundation Model Embedded within a Gypseous Soil Before and after Soaking - N.A. Ab-dullah; M.R. Mahmood; H.H. Baqir (Engineering and Technology Journal, 2017)
The paper explain an experimental study to show piled raft system behavior when embedded within gypseous soil in three different stats (dry, socking for 1 day and placing a bearing layer of dense sand below the gypseous soil when socking for 1 day). A small-scale “prototype” model of steel box with dimension of (60cm length x 60cm width x 75cm heights) was used for carried out the model tests. Two different lengths of reinforced concrete pile models (40cm and 45cm) of 2.0cm dia. were used to keep the same imbedded length ratio during testing piled raft and piles only. Three different configurations of pile groups (single, three and six piles) were tested in the laboratory in two ways, first; the raft does not contact with the soil and the second; the raft is in contact with the soil. In dry state, the gypseous soil showed a very high carrying capacity with reduction in settlement. Piled raft foundations show an efficient in dry state, where the load carrying capacity increased and the settlement decreased. The improvement ratios in the load carrying capacity were about 16% for single piled raft and 39% for group of three-piled raft, while settlement reduction ratios were about 18% for single piled raft and 45% for group of six-piled raft. When the gypseous soil socked with water for 1 day, the ultimate bearing capacity of foundations is generally reduced by about (69%-83%) compared with dry state for all model configurations. The improvement ratios in ultimate bearing capacity due to using piled raft in soaking state was about (11% -50%) whilst the reduction settlement ratios was about (16% -44%).